Mastócitos de Calomys callosus e Toxoplasma gondii: uma abordagem in vivo e in viiro de uma infecção experimental - Ferreira, Gabriela Lícia Santos (2001)
In Calomys callosus was studied: 1- the perítoneal exsudate mast cells, about its number in different times after Toxoplasma gondii infection, using chamber hemocytometer; 2- the ultrastructural caracteristics on the mast cells of the perítoneal exsudate, ear’s skin, submandibular and dorsal lymph nodes of the C. callosus-, 3- the mast cells behaviour in vivo in several organs (ear, ileum, submandibular and dorsal lymph nodes) after 48 hours of T. gondii infection using ultrastructural methods and also of the perítoneal exsudate mast cells using ultrastructural and histological methods; 4- the invasion capacity of the 7 gondii tachyzoites in perítoneal exsudate mast cells 12 hours after infection by a light and electron transmission microscopical; 5- interaction between mast cells and T. gondii in vitro using ultrastructural methods and assay/analysis imunofluorescent by a confocal microscopical. After 12 hours T. gondii infection we could see an increase in the amount of perítoneal exsudate mast cells, probably due a local proliferation and maturation of residing mast cells precursors. The mast cells from the exsudate perítoneal, ear’s skin, submandibular and dorsal lymph nodes of the C. callosus lias similar ultrastructural caracteristics between each other sliowing several/acountable citoplasmatic granules with homogeneus and electron dense content, in its majority. The mast cells from several organs (ears, ileum and submandibular and dorsal lymph nodes) of the C. callosus after 48 hours T. gondii infection and the mast cells from the perítoneal exsudate after 12 hours T. gondii infection presented a deep ultrastructural morphological changes suggesting a desgranulation process: citoplasmatic granules with a content of a little electron dense, fusion of the citoplasmatic granules, intracitoplasmatic channels, plasmatic membrane rupture and content of granules in the extracellular enviroment. This results suggests tliat the mast cells belong to the immunological answer against T. gondii infection. The tachyzoites intraperítoneally inoculated after 12 hours infection were fínd almost in its totality inside many kind of cells, including mast cells. The perítoneal exsudatemast cells of the C. callosus interation with parasites in vivo and presented morphological changes indicating desgranulation process, probably due this interation. This is the fírst work that describe the mast cell behaviour in vivo during the T. gondii infection.